CUSTOMER BEHAVIOR AS AN OUTCOME OF SOCIAL MEDIA MARKETING: THE ROLE OF CUSTOMER EXPERIENCE ON SKINCARE SALES ON SHOPEE - Pavitram, Sarasvati Devi Raja Guhyam; Iskandar, Muhammad Dhafi (International Journal Labs, 2025)
This study uses relationship quality as a mediating variable to examine how customers experience participation intention, loyalty, and purchase intention on Shopee for skincare items. Through an online survey, a 4-point Likert scale was used to gather primary data from citizens of Jakarta and Tangerang, aged 18 to 36. The findings demonstrate that satisfying interactions on Shopee social media considerably improve participation, loyalty, and intention to buy, while the quality of relationships increases consumer engagement. This study highlights the significance of personal connections, loyalty intention, and interactive content creation in increasing skincare sales. These implications are important to more successful e-commerce marketing methods, and more research is advised to include a larger sample and take into account other variables like promotions and customer reviews.